la inteligencia lingüística en el desarrollo de la lecto-escritura en los niños de educación inicial, de la Unidad Educativa Hispanoamérica de la ciudad de Ambato en el año lectivo 2015 – 2016” - Huaraca Marcatoma, Olga Patricia (2017)
The present research project is focused on determining the Linguistic Intelligence in the Development of Reading-writing in the children of Initial Education of the Educational Unit Hispanoamérica of the city of Ambato in the academic year 2015 - 2016. The design of research is non-experimental, type field, bibliographic of exploratory and descriptive level, with the following variables; Linguistic Intelligence as an independent variable and Reading-Writing Development as Dependent Variable, 25 children from a single parallel to were observed in the classroom by using an observation form. It was determined that it is necessary to develop reading and writing habits in children. Students need to master the four language skills: speaking, listening, reading and writing in order to develop a creative imagination and have the facility of forming sentences or groups of words with sense. Most of children do within and “expected” or “desired” time. A better reading-writing in children must be developed. Reading comprehension will lead them to access to science, art and technology. This will allow progress and human development which will bring both personal and social benefits according to the motivation that children receive at school age.